Hubungan antara Dukungan Keluarga dengan Kepatuhan Minum Obat pada Pasien Hipertensi - Kartika Fitri Diahastuti; Iskim Luthfa; Abrori (STIKes Ibnu Sina Ajibarang, 2025)
Hypertension is a chronic disease that requires long-term treatment. However, in reality, many patients remain non-adherent to their prescribed therapy. Non-adherence can lead to serious complications such as stroke, kidney failure, or heart disease. One of the crucial factors that can improve treatment adherence is family support. This support may include attention, supervision, motivation, and practical assistance such as reminding patients of their medication schedules. The aim of this study was to examine the relationship between family support and medication adherence among hypertensive patients at the Internal Medicine Specialist Polyclinic of RSSA Sangiang. This study employed a quantitative correlational design with a cross-sectional approach. A total of 189 respondents were recruited using consecutive sampling. The research instruments consisted of a family support questionnaire and the Morisky Medication Adherence Scale (MMAS-8) to assess adherence. Data were analyzed using the Spearman Rank test to determine the relationship between the two variables. The results showed that most respondents received family support at a moderate level (55.0%). Meanwhile, medication adherence among hypertensive patients was categorized as moderate in 49.2% of respondents. The Spearman test revealed a highly significant relationship between family support and medication adherence, with p=0.000 and a correlation coefficient r=0.832. In conclusion, family support plays a vital role in improving medication adherence among hypertensive patients. Therefore, healthcare providers are encouraged to involve families in the treatment process and provide continuous education to ensure adherence and prevent complications.